Effect of torrefaction temperature and HDPE binder addition on the physicochemical and combustion properties of elephant grass bio pellets - Nani Siska Putri Khan; Adi Setiawan; Lukman Hakim; Zulfikar Hasibuan; Shafira Riskina (Politeknik Negeri Lhokseumawe, 2026)
This study investigates the effect of torrefaction temperature and the addition of HDPE binder on the physical, chemical, and combustion properties of elephant grass (Pennisetum purpureum) biopellets. The samples were torrefied at 225°C and 275°C, with an HDPE plastic added at concentrations of 0, 5, 10, 15, and 20%. The results showed that higher torrefaction temperatures substantially reduced the solid yield due to the thermal decomposition of hemicellulose and cellulose, while simultaneously increasing fixed carbon and ash content. Apparent density and drop resistance showed a positive correlation with the addition of HDPE, indicating improved durability and structural integrity of the pellets. The hydrophobicity test revealed longer water penetration times with increasing HDPE content, demonstrating enhanced moisture resistance, although a slight decline was observed at 275°C due to polymer degradation. During combustion, pellets torrefied at 275°C exhibited a faster temperature rise and more stable mass reduction compared to those processed at 225°C, reflecting better combustion efficiency and heat transfer performance. The relationship between proximate analysis and combustion showed that lower Volatile Matter (VM) and higher fixed carbon contents contributed to improved thermal stability and controlled combustion behavior. These findings confirm that torrefaction at 275°C combined with a 15% HDPE binder produces high-quality biopellets with superior mechanical strength, hydrophobicity, and combustion performance, making them a promising candidate for sustainable and efficient bioenergy systems.